2013
DOI: 10.1007/s10815-012-9921-9
|View full text |Cite
|
Sign up to set email alerts
|

Balanced chromosomal translocations in men: relationships among semen parameters, chromatin integrity, sperm meiotic segregation and aneuploidy

Abstract: Abnormal semen parameters can serve as indicators of an additional risk of forming spermatozoa with defective chromatin and aneuploidy in translocation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 55 publications
(72 reference statements)
8
54
0
5
Order By: Relevance
“…This suggests that the breakpoint at 7p15 may not in fact affect spermatogenesis. Consistent with our findings, Vozdova et al (2013) reported a correlation between a 7q36 breakpoint and impaired spermatogenesis. And the associations between those at 7q21.2, 7q22, and 7q32 and recurrent abortion are also reported (Niroumanesh et al, 2011;Kochhar andGhosh, 2013, Zhang et al, 2015c).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the breakpoint at 7p15 may not in fact affect spermatogenesis. Consistent with our findings, Vozdova et al (2013) reported a correlation between a 7q36 breakpoint and impaired spermatogenesis. And the associations between those at 7q21.2, 7q22, and 7q32 and recurrent abortion are also reported (Niroumanesh et al, 2011;Kochhar andGhosh, 2013, Zhang et al, 2015c).…”
Section: Discussionsupporting
confidence: 92%
“…Carriers of reciprocal translocations, while phenotypically normal, may experience reduced fertility and spontaneous abortions (Harton and Tempest, 2012). Previous studies have reported the involvement of balanced reciprocal translocations on chromosome 7 in male infertility and recurrent miscarriage (Tharapel et al, 1985;Vozdova et al, 2013;Zhang et al, 2015c). In the current investigation, reciprocal translocation was identified in 82 (1.57%) infertile men, 14 of whom (17.07%) carried chromosome 7 translocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those parameters are lower than the rates mentioned in studies by Vozdova et al (30.8% of RT and 59.5% of RCT translocation carriers) [22] and the data presented by other authors [19]. This suggests that autosomal rearrangement of the karyotype does not always lead to severe oligozoospermia or azoospermia as do sex chromosome aberrations [5].…”
Section: Discussionmentioning
confidence: 62%
“…Other authors presented results showing no differences in terms of this sperm parameter between men with normal and abnormal karyotypes [29,30]. On the other hand, comparisons of RT carriers and control donors revealed decreased sperm motility in the group of patients carrying RT [18,19,22] for those with normal [19] and abnormal semen parameters [22]. Additionally, more recent data show only 4% progressive motility in 45,XY,t(14;14)(q10;q10) patients [31] and 8-17% progressive motility in 45,XY,t(14;22) patients [32].…”
Section: Sperm Motility (%)mentioning
confidence: 88%